Determination of the Instantaneous Noise Level Using a Discrete Road Traffic Flow Method - Algimantas DANILEVIČIUS; Irena DANILEVIČIENĖ; Mykola KARPENKO; Michał STOSIAK; Paulius SKAČKAUSKAS (Promet (Zagreb))
Noise pollution from the streets is a critical problem for those living or working near them. Although the traffic noise problem is not a new research topic, it is usually limited to providing average values. This paper aims to determine variations in the instantaneous noise level and its influencing factors using the experimental noise level and theoretical traffic flow using a discrete traffic flow model. The research results suggested that the noise level could be changed by properly managing traffic flow with existing traffic lights without changing the infrastructure. The results of this research may be useful for city transport traffic management institutions.